Synthesis of Lactulose in Batch and Repeated-Batch Operation with Immobilized ?-Galactosidase in Different Agarose Functionalized Supports - Vera-Vera, C (Elsevier Ltd, 2017)
Lactulose synthesis was done in repeated-batch mode with Aspergillus oryzae β-galactosidase immobilized in glyoxyl-agarose (GA-βG), amino-glyoxyl-agarose (Am-GA-βG) and chelate-glyoxyl-agarose (Che-GA-βG), at fructose/lactose molar ratios of 4, 12 and 20. Highest yields of lactulose in batch were obtained with Che-GA-βG (0.21, 0.29 and 0.32 g·g−1) for 4, 12 and 20 fructose/lactose molar ratios respectively; when operating in 10 repeated batches highest product to biocatalyst mass ratios were obtained with Am-GA-βG (1.82, 2.52 and 2.7 g·mg−1), while the lowest were obtained with Che-GA-βG (0.25, 0.33 and 0.39 g·mg−1). Operational stability of Am-GA-βG was higher than GA-βG and Che-GA-βG and much higher than that of the free enzyme, at all fructose/lactose molar ratios evaluated. Efficiency of biocatalyst use for GA-βG were 64.4, 35.5 and 18.4 kglactulose/gprotein, for fructose/lactose molar ratios of 4, 12 and 20 respectively, while for Che-GA-βG were 1.46, 1.05 and 0.96 kglactulose/gprotein. © 2017 Elsevier Ltd